Dendritic Cells in the Context of Human Tumors: Biology and Experimental Tools. (3rd March 2016) - Volovitz, Ilan; Melzer, Susanne; Amar, Sarah; Bocsi, József; Bloch, Merav; Efroni, Sol; Ram, Zvi; Tárnok, Attila
Abstract : Dendritic cells (DC) are the most potent and versatile antigen-presenting cells (APC) in the immune system. DC have an exceptional ability to comprehend the immune context of a captured antigen based on molecular signals identified from its vicinity. The analyzed information is then conveyed to other immune effector cells. Such capability enables DC to play a pivotal role in mediating either an immunogenic response or immune tolerance towards an acquired antigen. This review summarizes current knowledge on DC in the context of human tumors. It covers the basics of human DC biology, elaborating on the different markers, morphology and function of the different subsets of human DC. Human blood-borne DC are comprised of at least three subsets consisting of one plasmacytoid DC (pDC) and two to three myeloid DC (mDC) subsets. Some tissues have unique DC. Each subset has a different phenotype and function and may induce pro-tumoral or anti-tumoral effects. The review also discusses two methods fundamental to the research of DC on the single-cell level: multicolor flow cytometry (FCM) and image-based cytometry (IC). These methods, along with new genomics and proteomics tools, can provide high-resolution information on specific DC subsets and on immune and tumor cells with which they interact. The different layers of collected biological data may then be integrated using Immune-Cytomics modeling approaches. Such novel integrated approaches may help unravel the complex network of cellular interactions that DC carry out within tumors, and may help harness this complex immunological information into the development of more effective treatments for cancer.